SIGNS OF HOUSING AND HOUSEHOLD FORM OF SOCIAL PROTECTION OF EMPLOYEES OF PROSECUTION OFFICES OF UKRAINE - Омельяненко, Є. П. (Київський національний університет імені Тараса Шевченка, 2021)
The article presents a comprehensive analysis of the totality of features of housing and household for employees of the prosecutor's office in Ukraine. Among the main features of the housing and the household form of social protection is that, firstly, it is regulated by the provisions of the legislation in the housing sector (Housing Code of Ukraine), part 1 of Article 83 of the Law of Ukraine "On the Prosecutor's Office". Furthermore, this type of social protection is governed by separate legislation that governs housing and household supply for prosecutor's office staff at the bylaw level (mainly orders of the Prosecutor General and government resolutions). Secondly, the following types (directions) of objectification characterize this form of social protection: provision of office housing for employees of the prosecutor's office; and provision of material assistance for solving personal and household issues. The author draws attention to the fact that until December 6, 2019, the housing and household form of social protection for employees of the prosecutor's office in Ukraine also provided for the possibility of providing employees with an interest-free loan for housing construction or the purchase of apartments (individual residential buildings). The article concludes by summarizing the results of the study. They determine the prospects for improving the legislation in terms of the norms governing housing and social protection for employees of the prosecutor's office in Ukraine. The author substantiates the need to adopt a new Procedure for providing public servants (who need to improve housing conditions) with an interest-free loan for housing construction or the purchase of apartments (individual residential buildings). It is also stated that there is a need to limit managers' freedom in terms of satisfying the entitlement to material aid for resolving domestic and household concerns (to eliminate corruption risks in this field, suitable amendments should be made to the Procedure approved by the Resolution of the Cabinet of Ministers of Ukraine of 2016 No. 500).

Стаття присвячена комплексному аналізу сукупності ознак житлово-побутової форми соціального захисту працівників органів прокуратури в Україні. Серед основних ознак житлово-побутової форми соціального захисту називається те, що вона, по-перше, врегульовується положеннями законодавства у житловій сфері (Житловим кодексом України), ч. 1 ст. 83 Закону України «Про прокуратуру», а також спеціальним законодавством, яке врегульовує житлово-побутове забезпечення працівників органів прокуратури на підзаконному рівні (головним чином, накази Генерального прокурора та окремі урядові постанови). По-друге, ця форма соціального захисту об’єктивується в таких видах (напрямах): надання службового жилого приміщення працівникам органів прокуратури; надання матеріальної допомоги для вирішення соціально-побутових питань. Звертається увага на те, що до 6 грудня 2019 р. житлово-побутова форма соціального захисту працівників органів прокуратури в Україні передбачала також можливість надання і отримання безвідсоткового кредиту для житлового будівництва або придбання квартир (індивідуальних житлових будинків). У висновках до статті узагальнюються результати дослідження та окреслюються перспективи вдосконалення законодавства в частині норм, які регулюють житлово-побутову форму соціального захисту працівників  органів прокуратури в Україні. Автором обґрунтовується потреба в прийнятті нового Порядку надання державним службовцям, які відповідно до законодавства потребують поліпшення житлових умов, безвідсоткового кредиту для житлового будівництва або придбання квартир чи індивідуальних житлових будинків. Також наголошується на потребі звуження свободи керівників у відносинах з приводу задоволення права на матеріальну допомогу для вирішення соціально-побутових питань (внесення відповідних змін до Порядку, затвердженого постановою Кабінету Міністрів України 2016 р. № 500, з метою зниження корупційних ризиків в цій сфері).
ОЗНАКИ ЖИТЛОВО-ПОБУТОВОЇ ФОРМИ СОЦІАЛЬНОГО ЗАХИСТУ ПРАЦІВНИКІВ ОРГАНІВ ПРОКУРАТУРИ УКРАЇНИ
Keywords: employees of the prosecutor’s office; housing and household form of social protection; material assistance; office housing; social protection; social security.; житлово-побутова форма соціального захисту; матеріальна допомога; працівники органів прокуратури; службове житло; соціальна безпека; соціальний захист.